For Whom We Must Speak: Devising Actos for Undocumented Farmworkers - Levine, Annette; Castillo, Debra A. (Latin American Theatre Review, 2016)
In Spring 2015, Ithaca College’s IC Teatro (advised by Annette Levine), Cornell University’s Teatrotaller (Debra Castillo), the Teatro Travieso theatre company (Jimmy Noriega at College of Wooster), and Dartmouth College’s Analola Santana decided to collaborate on a homage to Teatro Campesino by working with our students to study the history of this important group and the current issues facing immigrant youth in our area and to devise new actos for presentation to our various communities. In this article, we explore what it means for our students to create devised work in this particular social justice context, where the central organizing problematic of the project requires them to speak, and moreover to speak for those who often are in no political or social position to speak for themselves, in full cognizance of the implications of speaking out in this artificial and ventriloquized manner. We offer our commentary on this project in a spirit of humility, knowing that many of our colleagues (perhaps most of us) have dealt with qualified success more often than not, and that there are important discussions that need to take place, and crucial pedagogical lessons to learn, from risking—and perhaps even courting—failure.